Wybrane metody statystyczne usprawniające efektywność badań w rolnictwie i gospodarce żywnościowej - Parlińska, Maria (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1995)
The paper presents current problems concerning Polish agriculture, namely export and ecological, environmental problems and others. Thus a review of known statistical methods and some new subjects are presented here.